Karawitan composition “Balengku” | Komposisi Karawitan Inovatif “Balengku” - I Komang Widiartha; Ni Putu Tisna Andayani (GHURNITA: Jurnal Seni Karawitan, 2023)
Balengku is an innovative musical composition by developing two different cultures. This material was created and inspired by the acculturation process in Lombok. Balengku's work was incorporated into the gamelan klentang media as the main instrument and added several gamelan instruments found in the gamelan gong kebyar barungan. The two instruments are combined to realize the concept of acculturation as a source of ideas in this work. This composition is realized using the Tri Angga structure and also gives a touch to the gending structure in Lombok. This Balengku material was made using qualitative methods through a process of observation, interviews, and also a literature study, then in the process of pouring ideas it was carried out using the exploration stage, improvisation stage and formation stage.